pWCP is a widely distributed and highly conserved Wolbachia plasmid in Culex pipiens and Culex quinquefasciatus mosquitoes worldwide - Amani Ghousein; Jordan Tutagata; Hans Schrieke; Manuel Etienne; Victor Chaumeau; Sebastien Boyer; Nonito Pages; David Roiz; A. Murat Eren; Guillaume Cambray; Julie Reveillaud (ISME Communications, 2023)
Abstract Mosquitoes represent the most important pathogen vectors and are responsible for the spread of a wide variety of poorly treatable diseases. Wolbachia are obligate intracellular bacteria that are widely distributed among arthropods and collectively represents one of the most promising solutions for vector control. In particular, Wolbachia has been shown to limit the transmission of pathogens, and to dramatically affect the reproductive behavior of their host through its phage WO. While much research has focused on deciphering and exploring the biocontrol applications of these WO-related phenotypes, the extent and potential impact of the Wolbachia mobilome remain poorly appreciated. Notably, several Wolbachia plasmids, carrying WO-like genes and Insertion Sequences (IS), thus possibly interrelated to other genetic units of the endosymbiont, have been recently discovered. Here we investigated the diversity and biogeography of the first described plasmid of Wolbachia in Culex pipiens (pWCP) in several islands and continental countries around the world—including Cambodia, Guadeloupe, Martinique, Thailand, and Mexico—together with mosquito strains from colonies that evolved for 2 to 30 years in the laboratory. We used PCR and qPCR to determine the presence and copy number of pWCP in individual mosquitoes, and highly accurate Sanger sequencing to evaluate potential variations. Together with earlier observation, our results show that pWCP is omnipresent and strikingly conserved among Wolbachia populations within mosquitoes from distant geographies and environmental conditions. These data suggest a critical role for the plasmid in Wolbachia ecology and evolution, and the potential of a great tool for further genetic dissection and possible manipulation of this endosymbiont.